2022
DOI: 10.1177/0306624x221086555
|View full text |Cite
|
Sign up to set email alerts
|

A Restorative Justice Intervention in United States Prisons: Implications of Intervention Timing, Age, and Gender on Recidivism

Abstract: Restorative justice seeks to balance the needs of the victim, offender, and community by repairing the harm caused by crime and wrongdoing and improving the prosocial competencies and accountability of the offender in response to an offense. Restorative justice interventions (RJIs) offer an alternative method to reduce harm and short- and long-term recidivism. However, empirical validation of mechanisms and moderating factors warrant additional inquiry within jail and prison settings. Thus, the authors sought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The relationship between age and recidivism has been supported by a substantial body of evidence (for a meta-analysis, see Piquero et al, 2015 ). Here, higher age has been consistently linked to lower levels of general recidivism (Craig, 2011 ; Olver and Wong, 2015 ; Ambroziak et al, 2021 ; Van Hall, 2023 ), as well as violent (Richner et al, 2023 ) and sexual recidivism (Barbaree et al, 2003 , 2009 ; Thornton, 2006 ; Nicholaichuk et al, 2014 ). This effect remained even when considering confounds, such as individuals' diagnoses of psychopathy (Olver and Wong, 2015 ), sexual arousal to offense-related stimuli (Barbaree et al, 2003 ), and when using brain-age measures, rather than chronological age (Kiehl et al, 2018 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The relationship between age and recidivism has been supported by a substantial body of evidence (for a meta-analysis, see Piquero et al, 2015 ). Here, higher age has been consistently linked to lower levels of general recidivism (Craig, 2011 ; Olver and Wong, 2015 ; Ambroziak et al, 2021 ; Van Hall, 2023 ), as well as violent (Richner et al, 2023 ) and sexual recidivism (Barbaree et al, 2003 , 2009 ; Thornton, 2006 ; Nicholaichuk et al, 2014 ). This effect remained even when considering confounds, such as individuals' diagnoses of psychopathy (Olver and Wong, 2015 ), sexual arousal to offense-related stimuli (Barbaree et al, 2003 ), and when using brain-age measures, rather than chronological age (Kiehl et al, 2018 ).…”
Section: Discussionmentioning
confidence: 95%
“…Our findings that females are significantly less likely to reoffend align closely with the results of previous research. A well-established line of work has repeatedly demonstrated that women are less likely than men to reoffend generally (Maden et al, 2006 ; Freeman and Sandler, 2008 ; Huebner and Pleggenkuhle, 2015 ; Richner et al, 2023 ), violently (for meta-analyses, see Cortoni et al, 2010 ; Piquero et al, 2015 ; see also McCarroll et al, 2000 ; Ménard et al, 2009 ), and sexually (for a meta-analysis, see Cortoni et al, 2010 ; see also Sandler and Freeman, 2009 ). Nevertheless, there has yet to be a clear consensus on an underlying mechanism or potential mediators for this gender difference.…”
Section: Discussionmentioning
confidence: 99%